Perubahan Kualitas Sperma Mencit (Mus musculus) Yang Terpapar Asap Rokok Elektrik - Andita Ayu Mandasari; Siti Nur Asiyah; Kurnia Lintang (Biotropic : The Journal of Tropical Biology, 2019)
Smoking is one of the habits that can affect human health. One type of cigarette that is currently the choice is electric cigarettes. The e-cigarette content includes nicotine, propylene glycol, flavorings and glycerin. The purpose of this study was to determine the effect of exposure to e-cigarette smoke on mice strain balb / c with the parameters of the number of spermatozoa. This study used 15 male mice which were 8-10 weeks old and weighed 25-30 grams of male mice which were divided into 3 treatment groups namely control group, treatment group one and treatment group two. In the control group no exposure to cigarette smoke was carried out while in the treatment group one was exposed to cigarette smoke in mice with a dose of 0 mg nicotine and the second treatment group was exposed to e-cigarette smoke at a dose of 18 mg nicotine. Electric cigarette smoke exposure is carried out for 30 days using a suction device from a syringe. The exposure of cigarette smoke is carried out every day with successive doses of 20 times as much as 3 times with a time lag of 10 minutes (5 minutes the chamber is closed and 5 minutes of the chamber is opened). The results showed that the average number of spermatozoa in the control group was 16.816 million / ml. The average number of spermatozoa in treatment one was 10.432 million / ml and the average number of spermatozoa in treatment two was 5.234 million / ml. This shows that exposure to cigarette smoke can reduce the number of spermatozoa from the control group to the first treatment by 42.56% and the second treatment shows a decrease from the first group by 34.65%.